2018
DOI: 10.1111/jvh.12991
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and diversity of hepatitis B and hepatitis delta virus in Gabon

Abstract: Although central Africa is classified as having a high endemicity of hepatitis B virus (HBV) and hepatitis D virus (HDV) infection, there is paucity of prevalence studies. For the first time on a country-wide level in Central Africa, we show in Gabon an overall 7.4% prevalence of Hepatitis B surface antigen (HBsAg) and that more than 25% of the HBsAg-positive population are infected by HDV. Although HBV prevalence did not differ significantly between provinces, there is a north-south split in the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
8
15
0
Order By: Relevance
“…In Cameroon, the highest HDV prevalence was seen in the Southern part of the country, under latitude 4° N, with a sub-equatorial climate and largely forested areas. Similar high HDV prevalence were observed through populational studies in neighbouring regions of Gabon (63%–66% in the Northern region called Woleu-Ntem),21 25 26 and investigation of icteric patients in Democratic Republic of Congo (33% and 48% in the Northern regions of Equator and Orientale, respectively) 27. In a similar manner, migrants from Equatorial Guinea in Spain presented high rates of HDV seropositivity (24%) 28.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In Cameroon, the highest HDV prevalence was seen in the Southern part of the country, under latitude 4° N, with a sub-equatorial climate and largely forested areas. Similar high HDV prevalence were observed through populational studies in neighbouring regions of Gabon (63%–66% in the Northern region called Woleu-Ntem),21 25 26 and investigation of icteric patients in Democratic Republic of Congo (33% and 48% in the Northern regions of Equator and Orientale, respectively) 27. In a similar manner, migrants from Equatorial Guinea in Spain presented high rates of HDV seropositivity (24%) 28.…”
Section: Discussionsupporting
confidence: 76%
“…Some previous large-scale studies of HDV in Africa were conducted in The Gambia and Burkina Faso, where only ≈1% of HBsAg carriers are HDV-seropositive, precluding the evaluation of risk factors for HDV infection 19 20. In Gabon, a study of 4107 persons living in rural villages identified 303 HBsAg antigenemic participants, of whom 84 (28%) were HDV seropositives 21. With a large representative sample of the adult population of Cameroon, this study revealed an extreme degree of heterogeneity of HDV distribution across Cameroon, ranging from 1% to 54% according to regions, with the highest prevalence found in the Southern regions close to the Equator.…”
Section: Discussionmentioning
confidence: 99%
“…Besombes et al were able to demonstrate that high HBsAg-seroprevelance (as observed in Northern Cameroon) does not always translate to high HDV seroprevalence (as observed in Southern Cameroon). These findings are in line with those of another recent study from the region in which a very similar pattern of HDV infection was demonstrated in a nationally representative sample of Gabon 5. Both studies found a prevalence close to 70% in areas situated at the same latitudes and a decreasing prevalence further away from the epicentre.…”
supporting
confidence: 92%
“…HDV seroprevalence in Cameroon was 10.6% in 1,621 unselected HBsAg-positive individuals in 2011 68 and 46.7% in 1,928 HBsAg-positive hospital patients in 2010 to 2016, 69 while it was 27.7% in 303 HBsAg carriers between 2005 and 2008 in Gabon. 70 In both countries there were large regional variations. In the Central African Republic, 50% of patients with chronic HBsAg-positive hepatitis and hepatocellular carcinoma (HCC) were anti-HD positive between 1998 and 2010 71,72 and, in the Democratic Republic of Congo, 26.1% of HBsAg-positive patients with jaundice were seropositive in 2017.…”
Section: Key Pointmentioning
confidence: 99%